1988
DOI: 10.1097/00006842-198803000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Type A behavior and angiographically documented coronary atherosclerosis in a sample of 2,289 patients.

Abstract: To determine the relationship between Type A behavior pattern and angiographically documented coronary atherosclerosis (CAD), we analyzed risk factor, behavioral, and angiographic data collected on 2,289 patients undergoing diagnostic coronary angiography at Duke University Medical Center between 1974 and 1980. Multivariable analyses using ordinal logistic regression techniques showed that Type A behavior as assessed by the structured interview (SI) is significantly associated with CAD severity after age, sex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(52 citation statements)
references
References 0 publications
8
42
2
Order By: Relevance
“…Finally, the associations thus described in the above hypotheses will be observed primarily in younger patients. The rationale for the third hypothesis is based on a recent study of 2289 patients in which an association between TABP and CAD severity was obtained only in younger patients (19). Thus, older patients may reflect a group of particularly hardy survivors in which psychosocial influences on disease are resisted by constitutional makeup.…”
mentioning
confidence: 99%
“…Finally, the associations thus described in the above hypotheses will be observed primarily in younger patients. The rationale for the third hypothesis is based on a recent study of 2289 patients in which an association between TABP and CAD severity was obtained only in younger patients (19). Thus, older patients may reflect a group of particularly hardy survivors in which psychosocial influences on disease are resisted by constitutional makeup.…”
mentioning
confidence: 99%
“…On the one hand, there is some evidence that Type A behaviour is not really very toxic and that it does not necessarily lead to CHD (Ben-Zur, 2002;Dembroski & Costa, 1988;Dembroski, MacDougall, Costa & Grandits, 1989;Haynes & Matthews, 1988;Huysamen, 1994;Lutz, Holmes & Cramer 1987;Williams, Barefoot, Haney & Harrell, 1988).…”
Section: Opposing Views On Type Amentioning
confidence: 99%
“…n.s., no significant Means, mean NK activity of patients with CHD split by the presence of each risk factor hostility, and angiographically documented coronary atherosclerosis, 15 or reported a relationship between the hostility scale in the Minesota Multiphasic Personality Inventory (MMPI) and mortality rates from arteriosclerosis and CHD. 16 Thus, anger and aggressiveness are considered to be important factors in the development of coronary arteriosclerosis and CHD.…”
Section: Psychological Factors and Chdmentioning
confidence: 99%
“…[11][12][13][14] However, in the 1980s an increased number of studies indicated that anger and hostility were directly related to CHD. 15,16 Thus, TABP, as initially conceptualized, is a broad behavioral and emotional syndrome, but anger or hostility is more strongly correlated with CHD than the other aspects of TABP. Hostility is also related to atherosclerosis independently of TABP.…”
Section: Introductionmentioning
confidence: 99%